Bupleurum in Treatment of Depression Disorder: A Comprehensive Review - Shuzhen Ran; Rui Peng; Qingwan Guo; Jinshuai Cui; Gang Chen; Ziying Wang (MDPI AG, 2024)
The incidence of depression has been steadily rising in recent years, making it one of the most prevalent mental illnesses. As the pursuit of novel antidepressant drugs captivates the pharmaceutical field, the therapeutic efficacy of Traditional Chinese Medicine (TCM) has been widely explored. Chaihu (Bupleurum) has been traditionally used for liver conditions such as hepatitis, liver inflammation, liver fibrosis, and liver cancer. It is believed to have hepatoprotective effects, promoting liver cell regeneration and protecting against liver damage. In addition, Bupleurum has also been used as a Jie Yu (depression-relieving) medicine in China, Japan, Republic of Korea, and other Asian countries for centuries. This review article aims to summarize the research conducted on the antidepressant properties and mechanisms of Bupleurum, as well as discuss the potential of TCM formulas containing Bupleurum. This review highlights various antidepressant ingredients isolated from Bupleurum, including saikosaponin A, saikosaponin D, rutin, puerarin, and quercetin, each with distinct mechanisms of action. Additionally, Chinese herb prescriptions and extracts containing Bupleurum, such as Chaihu Shugansan, Xiaoyaosan, and Sinisan, are also included due to their demonstrated antidepressant effects. This review reveals that these Bupleurum compounds exhibit antidepressant effects through the regulation of neurotransmitter mechanisms (such as 5-HT and DA), the NMDA (N-methyl-D-aspartate) system, brain-derived neurotrophic factor (BDNF), and other intracellular signaling pathways. Collectively, this comprehensive review provides insights into the multiple applications of Bupleurum in the treatment of depression and highlights its potential as an alternative or complementary approach to traditional therapies. However, it is essential to consider the potential adverse effects and clinical restrictions of Bupleurum despite its promising potential. Further research is needed to elucidate its specific mechanisms of action and evaluate its effectiveness in human subjects.